Analysis of Factors that Affect the Performance of Accounting Information Systems at Bapenda Bali - Pratiwi, Putu Indah Cahya; Putra, I Made Pande Dwiana (E-Jurnal Akuntansi; Vol 35 No 5 (2025)DO - 10.24843/EJA.2025.v35.i05.p17, 2025)
This research aims to achieve consistency by retesting previous studies and understanding the factors that influence the performance of the accounting information system at the Bali Province Regional Revenue Office (Bapenda). The population in this study consists of all users of the Accounting Information System (AIS) at the Bali Province Regional Revenue Office, using a saturated sampling technique. Therefore, the entire population, consisting of 44 employees, is used as the research sample. The analytical technique employed is Multiple Linear Regression Analysis processed using SPSS Version 26. The implications of this research provide evidence and understanding regarding the positive influence of training and education programs, as well as personal technical capabilities, on the performance of the accounting information system. The better the training and education programs attended by employees, and the stronger the technical capabilities possessed by employees, the better the performance of the accounting information system at the Bali Province Regional Revenue Office. However, leadership support has been shown to have no significant impact on the performance of the accounting information system due to the insufficiency of support provided by leadership if not accompanied by proper implementation of the system's utilization. Keywords: Accounting Information System; Employee Performance.